Mucinous Histology Might Be an Indicator for Enhanced Survival Benefit of Chemotherapy in Stage II Colon Cancer - Huang, Yong; Ge, Kuanxue; Fu, Guangshun; Chu, Junfeng; Wei, Wei (Frontiers in Medicine, 2020)
Background It was a difficult question to identify candidates who would benefit most from adjuvant chemotherapy in stage II colon cancer because of the paucity of relevant conclusive clinical trial results. We aimed to assess if mucinous adenocarcinoma (MUA) could be an indicator for the efficacy of adjuvant chemotherapy in stage II colon cancer. Methods Using SEER*Stat software V.8.3.5, eligible patients were then recruited from the SEER database. Chi-square test was applied to compare the distribution of different categorical variables between non-mucinous adenocarcinoma (NMUA) and MUA groups. We then used the Kaplan-Meier method to analyze OS of different histological types in stage II colon cancer, and the log-rank test was then used to assess the OS differences. The Cox proportional regression risk models were also built in our analyses to eliminate potential crossed bias from other prognostic factors. Results A total of 50065 patients diagnosed with stage II colon cancer were recruited from the SEER database from 2004 to 2011, all the patients were divided into two groups, including NMUA (N = 44785) and MUA (N = 5280). The Cox analysis of the histological type indicated that the survival difference between MUA and NMUA failed to reach statistical significance in stage II colon cancer (P = 0.360). In NMUA, patients treated with adjuvant chemotherapy were independently associated with 37.2% decreased risk of overall mortality compared with those not (HR = 0.628, 95%CI = 0.601-1.656, P <0.001); in MUA, the number increased to 41.5% (HR = 0.585, 95%CI = 0.515-0.665, P <0.001). Conclusions Our study showed that the survival difference between MUA and NMUA failed to reach statistical significance in stage II colon cancer. More importantly, our study had provided the first evidence that chemotherapy would offer higher survival improvement in MUA compared with NMUA in stage II colon cancer, mucinous histology might be an indicator for enhanced survival benefit of chemotherapy in stage II colon cancer.